2022
DOI: 10.1039/d1ta10723b
|View full text |Cite
|
Sign up to set email alerts
|

NiCo (oxy)selenide electrocatalysts via anionic regulation for high-performance lithium–sulfur batteries

Abstract: The sluggish redox kinetics and shuttle effect of polysulfides, difficult oxidation process of Li2S severely hinder practical application of Li-S batteries, in which electrocatalysts with highly intrinsic activities are essential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Recent studies have shown that cationic regulation can vary the electronic structure and regulate the electron density of the catalysts to maximize adsorption states and charge transfer capabilities. 29–31 Ru doping into CeO 2 may alter the electronic structure of CeO 2 , boosting the intrinsic activity of active sites, hence enhancing reversible anion redox of lithia-based cathode. In addition, the number of oxygen vacancies in CeO 2 can be considerably increased by Ru doping, thereby allowing reversible anion-redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that cationic regulation can vary the electronic structure and regulate the electron density of the catalysts to maximize adsorption states and charge transfer capabilities. 29–31 Ru doping into CeO 2 may alter the electronic structure of CeO 2 , boosting the intrinsic activity of active sites, hence enhancing reversible anion redox of lithia-based cathode. In addition, the number of oxygen vacancies in CeO 2 can be considerably increased by Ru doping, thereby allowing reversible anion-redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…2c, two pairs of redox peaks can be observed for the Mo 0.3 NiCo 2 Cl LDH electrode and the potential difference between these oxidation-reduction peaks is small, which means the good reversibility of the redox reaction. 32 The relationship between scanning rate (v) and peak density (i) obeys the following power-law relationship:…”
Section: Resultsmentioning
confidence: 99%
“…2c, two pairs of redox peaks can be observed for the Mo 0.3 NiCo 2 Cl LDH electrode and the potential difference between these oxidation–reduction peaks is small, which means the good reversibility of the redox reaction. 32 The relationship between scanning rate ( v ) and peak density ( i ) obeys the following power-law relationship: 33 i = av b where the b value of 1.0 represents capacitive-like behavior and the b value of 0.5 indicates that the electrochemical redox reaction is controlled by a diffusion process. For the NiCo 2 Cl cathode, the calculated b values are 0.51 and 0.57 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, two distinct discharge platforms can still be observed when the current reaches 5 C, revealing that the O V -NiCo 2 O 4 //PP battery has excellent sulfur reaction kinetics. 37 The cycling performance of the O V -NiCo 2 O 4 //PP battery and the PP battery was investigated and is shown in Fig. 6a.…”
Section: Dalton Transactions Papermentioning
confidence: 99%